Perinatal hypothalamic-pituitary-adrenal axis regulation among women with eating disorders and their infants. (February 2017) - Easter, A.; Taborelli, E.; Bye, A.; Zunszain, P.A.; Pariante, C.M.; Treasure, J.; Schmidt, U.; Micali, N.
Highlights: Eating disorders can affect pregnancy outcomes and impact on child development. Foetal programming is a potential mechanism for these outcomes. During pregnancy women with eating disorders show blunted diurnal cortisol rhythms. In the postnatal period their infants also have a heightened response to stress. Indicating intergenerational effects of hypothalamic-pituitary-adrenal axis dysfunction. Abstract: Background: Psychiatric illness is associated with heightened hypothalamic-pituitary-adrenal (HPA) axis activity during pregnancy which may have long term effects on infant stress regulation. HPA axis regulation has not previously been investigated in women with eating disorders (ED) or their infants during the perinatal period. Methods: Women were recruited to a prospective longitudinal study in three groups: 1) current or active ED (C-ED = 31), 2) past ED (P-ED = 29) and healthy control (HC = 57). Maternal psychopathology, diurnal cortisol levels, corticotropin-releasing hormone (CRH) and CRH binding protein (CRH-BP) were measured during the third trimester of pregnancy. At eight weeks postpartum infant cortisol was obtained before and after routine immunisations to determine infant hormonal response to a stressful situation. Results: Women with current ED had a significantly lower cortisol decline throughout the day compared to HC, in both adjusted and unadjusted analyses. Lower cortisol decline among women with a current ED were associated with higher levels of psychopathology during pregnancy. Women's cortisol awakening response, CRH and CRH-BP levels did not differ across the three groups. Infants' stress response was also significantly higher among those in the C-ED group, although this effect was attenuated after controlling for confounders. Conclusions: During pregnancy women with ED have lower cortisol declines, suggestive of blunted diurnal cortisol rhythms. Postnatally, their infants also have a heightened response to stress. This is the first study to identify HPA axis dysfunction in pregnancy in women with ED, and to show an intergenerational effect. Since dysfunctions in HPA activity during childhood may represent a risk factor for psychological and physical health problems later in life, further investigation of the potential long-term implications of these findings is crucial.